Tunable Multiband Microstrip Antenna for 5GHZ WLAN (Global Journals of Research in Engineering, 2013)
In this paper, a tunable Multiband Micro strip Antenna is designed, capable of tuning its operating frequency in 5GHz band independently. Two slots of E U shape are etched to achieve multiband resonance. Two capacitors of fixed value and a varactor diode are used to achieve tuning. Proposed antenna targets the 5GHz WLAN bands; UNII-1 and UNII-2. Simulated and measured results are in good agreement.
Keywords: reconfigurable antenna; fr reconfigurability; variable reactive loading; 5ghz Wlan